Effect of chain wheel shape on crank torque, freely chosen pedal rate, and physiological responses during submaximal cycling - Hansen, E. A.; Jensen, K.; Hallen, J.; Rasmussen, J.; Pedersen, P. K. (Journal of Physiological Anthropology, 2009)
The development of noncircular chain wheels for the enhancement of cycling performance has been in progress for a long time and continues apace. In this study we tested whether submaximal cycling using a non-circular (Biopace) versus a circular chain wheel resulted in lower peak crank torque at preset pedal rates as well as resulting in lower pedal rate and metabolic response at freely chosen pedal rate. Ten trained cyclists (mean±SD: 27±3 years of age, 182±4 cm tall, 77.5±7.0 kg of body mass, and peak oxygen uptake of 61.7±4.4 ml kg-1 min-1) cycled with a Biopace and a circular chain wheel at 180 W at 65 and 90 rpm for recording of crank torque profiles, and at their freely chosen pedal rate for recording of pedal rate and metabolic response, including oxygen uptake and blood lactate concentration. Crank torque profiles were similar between the two chain wheels during cycling at preset pedal rates. During cycling at the freely chosen pedal rate (being 93±6 and 93±4 rpm for the Biopace and circular chain wheel, respectively), blood lactate concentration was significantly different between the two chain wheels, being on average 0.2 mmol l-1 lower with the Biopace chain wheel. A musculoskeletal simulation model supported the idea that a contributing factor to the observed difference in blood lactate concentration may be slightly reduced muscle activity around the phase where peak crank torque occurs during cycling with the Biopace chain wheel. In that particular phase of the crank revolution, the observed slightly lower muscle activity may result from larger transfer of energy from the legs to the crank.